Between Nationalism and Continentalism: State Auto Industry Policy and the Canadian UAW, 1960-1970 - Anastakis, Dimitry (Labour/Le Travailleur, 2004)
Abstract In the turbulent 1960s Canadians debated foreign control of the Canadian economy and Canada’s relations with the United States. The Canadian section of the United Auto Workers (UAW) also struggled with these questions as it faced a number of government policies designed to bolster the auto industry and solve balance of payments difficulties, culminating in the 1965 Canada-United States Auto motive Products Trade Agreement (auto pact). The auto pact rationalized the Canadian Big Three (General Motors, Ford, and Chrysler) production into their parent corporations and by 1970 the Canadian industry was fully integrated into a continental system of North American automobile manufacturing. The Canadian UAW played an ineffectual role in shaping this transformation, one which rekindled and exacerbated conflict within the membership and between militant locals and the union’s leadership. Nonetheless, by the end of the decade, the union had become a strong advocate of the new continental auto regime, a reflection of the increased employment and production resulting from the changes. The essay explains the issues the union faced in this period and some of the long-term consequences which the continentalization of the auto industry had on the union.